O discurso dos profissionais sobre a relação com os usuários no serviço de radiologia - Tavares, Renata Tôndolo (Universidade do Vale do Rio do Sinos, 2007)
The humanizing term, used constantly in the area of the health, is the solid basis of innumerable qualifying actions for qualification of the assistance as a whole. The radiology itself as a part of the suit still little is explored. The subject was argued from the meeting of focal groups composite for professionals of the area. The used referencial was of the practical discursive and from the worker´s interviews we could identify two main interpretative repertoires: the empiricist, that are the vision idealized for the groups, and the contingent that the practical reality reflects lived in the daily one. The variabilities gifts in the speeches had been salient in order to evidence these contradictions. This research analyzes the humanization of radiology from the speech of its professionals making an analogy to the box of Pandora and its mysterious content, in order to evaluate its practical and to plan future actions.
Keywords: análise do discurso; humanização; radiologia; tecnologias; hospital; discourse analysis; humanization; radiology; thecnologies; hospital; Ciências da Saúde